POTENSI ECENG GONDOK (Eichhornia crassipes) FERMENTASI SEBAGAI PAKAN ALTERNATIF TERNAK RUMINANSIA - Asrul Asrul; Ima Malawati (Agrienvi: Jurnal Ilmu Pertanian, 2023)
Feed is one of the essential factors in livestock business. In an effort to meet the basic needs of livestock and reduce the production costs of livestock business, it is necessary to have alternative feed ingredients. Water hyacinth is an aquatic plant that grows wild in lakes, rivers and swamps. Water hyacinth in the Kupang area, especially in the Tilong Dam and Raknamo Dam areas, thrives and is considered a plant that often damages the environment because it can reduce the amount of water and block irrigation channels. high economic value. This study aims to examine the content of nitrogen, phosphate and total energy of water hyacinth and henceforth with the potential of these nutrients it is hoped that they can become alternative feed in the form of silage for ruminants, especially livestock in Kupang City. Test results for the content of nitrogen, phosphate and total energy of water hyacinth, showed that water hyacinth which was not given EM4 and which was given EM4 during the fermentation process showed no significant difference. Water hyacinth that received 7% EM4 treatment showed better results on Nitrogen content (1.15%) and Total Energy (3362 Kcal/kg) than those that did not get EM4 addition treatment, namely 1.04% for Nitrogen content and 3281 Kcal/kg for Total Energy. For the parameter of phosphate content produced fermented water hyacinth without using EM4 showed better results than that given EM4, namely 0.42% for water hyacinth without the addition of EM4 and an average of 0.31% for water hyacinth with the addition of EM4. The conclusion of this study is that water hyacinth has potential as an alternative feed ingredient.